Prevenção e promoção da saúde no contexto organizacional: percepção da doença, estresse e bem-estar subjetivo de trabalhadores hipertensos e normotensos - Pires, Gerusa Estelita da Silva (Universidade do Vale do Rio dos Sinos, 2017)
This thesis is composed of two empirical articles, part of a research project regarding the illness perception, perceived stress and subjective well-being of hypertensive and normotensive workers. In the first paper, were examined the illness perception, stress levels and subjective well-being of the participants and the relationship between these constructs. In the second paper, a pilot intervention protocol was developed and tested, to evaluate its effects on the illness perception and stress management. Both studies were quantitative, being the first a cross-sectional correlational and the second a quasi-experimental design. The participants were 33 workers, divided into hypertensive and normotensive. The instruments used for both studies were biosociodemographic/health behaviors questionnaire, Brief illness perception and Perceived stress scales, additionally PANAS and Life satisfaction scales were used for study 1. In study 1, the results revealed that hypertensive perceived the illness as non-threatening, whereas normotensive perceived hypertension as slightly threatening. In addition, both groups believed that the individual and the treatment have great importance to control the disease. Normotensive had high perception that the illness is symptomatic (identity) and that it causes many consequences for the patient’s life. The results also indicated moderate levels of life satisfaction, stress and positive affect, while the levels of negative affect were low for men and moderate for women. These results allowed a better understanding about illness perception, stress and subjective well-being of hypertensive and normotensive workers, highlighting that both groups were different in terms of illness perception, but similar in levels of subjective well-being and stress. In study 2, the results demonstrated the positive effects of the intervention in both groups, especially through the reduction of stress levels and the increase in the perceptions of comprehension (coherence) and personal control about the illness. These results reinforce the importance of health education as a strategy to promote individual autonomy, aiming the prevention and control of hypertension. In addition, the findings indicated that due to the difference of both clinical conditions, it’s important to personalize future interventions as per the specific needs of each group. The findings of both studies may be useful for planning future strategies for the prevention and control of hypertension with the general population, but especially with workers from different segments.
Keywords: Doenças; Estresse; Hipertensão; Aspectos psicossomáticos; Trabalhadores hipertensos; Trabalhadores normotensos; Bem-estar; Saúde; Illnesses; Stress; Hypertension; Psychosomatic aspects; Hypertensive workers; Normotensive workers; Welfare; Health; ACCNPQ::Ciências Humanas::Psicologia